A Digital Tool to Build the Capacity of Leaders to Improve Working Conditions Related to Psychological Health and Well-Being in Teams: Intervention Approach, Prototype, and Evaluation Design of the Web-Application “wecoach” - Grimm, Luisa A.; Bauer, Georg F.; Jenny, Gregor J. (Frontiers in Public Health, 2020)
The “wecoach” is a web-application that builds the capacities of team leaders to improve working conditions that are positively related to the psychological health and well-being of their team members. The web-application works through an automated, rule-based chat enhanced by machine learning. This so-called conversational agent guides the team leader through a systematic project cycle, providing a mind map of work and health, training materials, self-assessments, and online tools to conduct team surveys and workshops, as well as self-evaluation of progress and effectiveness. In this paper, we present the development process of this web-application, which resulted in (1) a comprehensive intervention approach, (2) the prototype, and (3) the implementation of an evaluation design for a multi-level, randomized controlled trial.